Infertilidade masculina: com oligozoospermia estudo citogenético em indivíduos ou azoospermia - Curado, Roberta Machado de Oliveira Frota (2015)
Male infertility affects about half of couples with infertility history and is considered a multifactorial syndrome, including a broad spectrum of diseases. Chromosomal abnormalities are a major cause of human infertility and interfere with spermatogenesis. Infertility in patients with Klinefelter's syndrome (KS) is a consequence of degeneration of germ cells and that affects about 4% of infertile men. Objective: To investigate the presence of chromosomal abnormalities in infertile men with azoospermia or oligozoospermia seen at the Human Reproduction Laboratory of the Hospital das Clinicas (LabRep -HC) of the Federal University of Goiás, in 2013. Methodology: Descriptive study. Metaphases were analyzed in GTG bands obtained from lymphocytes cultures of 20 infertile men idiopathic causes. Results: The patients' ages ranged from 26-59 years and the design attempts ranged on average of 5 (± 5.02) years. In 3/20 (15%) patients were found karyotype 47, XXY (SK) and the rest, 17/20 patients had a normal karyotype. Conclusion: Genetic testing can help identify which patients would benefit from the technical reproduction. These studies are relevant because the assisted reproduction techniques ignore the process of natural selection and some classic chromosomal abnormalities end some deleterious mutations that could through generations. Thus, genetic assessment can lead to genetic counseling and hence the primary and secondary prevention of congenital defects in offspring of patients with male infertility. This study helps to assess the prevalence of chromosomal abnormalities in some men treated at LabRep - HC UFG.